Computer-aided design of post-tensioned, prestressed concrete flat slab and flat plate by the ACI 318-71 - Coo, Benito K.
The purpose of this thesis is to provide a computer program for the analysis and design of prestresses post-tensioned frame by ACI 318-71. The stiffnesses of columns and slabs are computed using equivalent frame method. The slope-deflection method and statics are used to derive the structure stiffness matrix equation for the frame which is specifically a traditional matrix. Fixed-end moments are computed using the column analogy method. Rotations are computed using a special simultaneous equation solver for tridiagonal systems. End moments are obtained by back substituting rotations into slope-deflection equations.